Humanisme sebagai Etika Politik: Relasi Negara dan Agama dalam Pemikiran Abdurrahman Wahid - Widya Rahmalestari; Aswar; Fiqi Restu Subekti (MAN 4 Kota Pekanbaru, 2026)
This study examines Abdurrahman Wahid’s (Gus Dur) thought on humanism as a foundation of political ethics in the relationship between the state and religion. The aim of this research is to explain how humanism in Gus Dur’s intellectual framework functions as a moral principle that both limits state power and prevents religion from being instrumentalized as a source of political legitimacy. Employing a qualitative approach, this study applies textual analysis to Gus Dur’s major works, particularly “Tuhan Tidak Perlu Dibela” and “Islamku, Islam Anda, Islam Kita”, supplemented by secondary literature. The findings indicate that Gus Dur conceives the state as a worldly institution whose primary responsibility is to safeguard human dignity, social justice, and freedom of religion, without intervening in the domain of theological truth. In this framework, religion serves as a source of ethical values rather than as a state ideology. The novelty of this study lies in articulating Gus Dur’s theistic humanism as a political-ethical framework that rejects both religious formalism and extreme secularism, thereby offering a mediating perspective for governing public life in a plural society. This study underscores the continued relevance of Gus Dur’s thought for strengthening inclusive political ethics in contemporary Indonesia.